Are student jobs flexible jobs? Using online data to study employers' preferences in Slovakia - Lucia Mýtna Kureková; Zuzana Žilinčíková (IZA Journal of European Labor Studies, 2016)
This paper analyses patterns of student employment in Slovakia where the numbers of university graduates have risen significantly. We use online job vacancy data and compare 'student jobs' and 'flexible jobs' to understand differences and similarities between the student and flexible labour markets that are often seen as identical. We find substantive differences in the required skill profiles between student-focused vacancies and those based on flexible forms of contract. In addition, student-targeted vacancies can be found across the occupational ladder, which refutes propositions that the student labour market is only precarious, temporary and part-time. From a policy perspective, our findings imply that any regulation of the flexible labour market will only partially address the student labour market.
Keywords: J23; J21; J24; J63; 330; Youth; Students; Employers; Flexible labour market; Big data; Skills Slovakia